Early results of laparoscopic single‑anastomosis duodeno‑ileal bypass with sleeve gastrectomy: a case series from a single Polish bariatric center - Mateusz Wityk; Maciej Bobowicz; Mateusz Pryt; Natalia Dowgiałło-Gornowicz (Videosurgery and Other Miniinvasive Techniques)
Introduction: The obesity epidemic has led to an increased prevalence of related conditions, such as type 2 diabetes (T2D) and hypertension. While laparoscopic sleeve gastrectomy is the most common metabolic bariatric surgery, up to 50% of patients may require revisional procedures due to weight regain or comorbidity recurrence. Single-anastomosis duodeno-ileal bypass with sleeve gastrectomy (SADI-S) is emerging as an effective treatment option with promising short-term outcomes.